COMMUNICATION APPROACHES FOR PROMOTING SCHOOL ENROLMENT IN RURAL COMMUNITIES: A STUDY OF ASA LOCAL GOVERNMENT AREA, KWARA STATE, NIGERIA - Olubukola Adenaiye, Happiness; Damilola Kolade, Rachael; Adewunmi Oyeduntan, Enoch (African Journal of Social and Behavioural Sciences, 2026)
In Nigeria, despite government efforts to achieve universal basic education, enrolment rates in many rural areas remain below national expectations. Communication plays an important role in influencing educational participation through community engagement, behavioural change, and social mobilization; however, its effectiveness in rural Nigerian contexts remains insufficiently explored. This study examined communication approaches used to promote school enrolment in Asa Local Government Area of Kwara State, Nigeria. The study was guided by the Diffusion of Innovations Theory and Social Mobilization Theory and adopted a sequential explanatory mixed-methods design. Data were collected through a structured questionnaire administered to 420 respondents selected using stratified random sampling, of which 384 questionnaires were successfully returned and found usable for analysis. In addition, in-depth interviews were conducted with purposively selected community stakeholders. Quantitative data were analysed using descriptive statistics, chi-square tests, and linear regression, while qualitative data were analysed thematically. The findings showed that interpersonal communication, particularly through community meetings and opinion leaders, was the most effective strategy for encouraging school enrolment. In contrast, formal mass media campaigns had limited reach and influence on parental decisions. The study also identified several barriers to enrolment, including low parental literacy, economic hardship, cultural preferences for male education, and distrust of government communication channels. Furthermore, community mobilization involving religious leaders and traditional rulers significantly influenced enrolment decisions and improved community participation in educational initiatives. The study concludes by recommending greater reliance on community-based communication strategies and stakeholder engagement to improve school enrolment and bridge educational gaps in rural Nigeria.